(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Objectives: To see the common indications of tracheostomy in ICU in this country, to compare the benefits over endotracheal intubation and to find out the pattern of complication of tracheostomy in the ICU to enrich the ideas for minimizing the complications. Methods: This is a cross sectional study was carried out at the Department of Otolaryngology and Head-Neck Surgery and Intensive Care Unit of Bangabandhu Sheikh Mujib Medical University & Dhaka Medical college Hospital, Dhaka from October 2012 to march 2013.This study includes all ICU patients, irrespective of age and sex, whose tracheostomy has done after admission in Intensive Care Unit. Results: The study revealed that the commonest indication of tracheostomy in the ICU was head injury with history of RTA (27.5%), followed by post operative case of Intracranial space occupying lesion (25%). Next common indications were Guillain-Barre syndrome (15%), cerebrovascular accident (12.5%), Maxillofacial trauma (5%), RTA with cervical spinal cord injury (5%), and post operative pneumonia (5%)., Regarding benefits of tracheostomy over endotracheal intubation in ICU we found that 100% patient had greater comfort.The rate of complication of tracheostomy in ICU was 10% in this study. Surgical emphysema was the commonest complications (5%) followed by haemorrhage(2.5%) and tube displacement(2.5%). Bangladesh J Otorhinolaryngol; April 2015; 21(1): 28-32